Constructing China : clashing views of the People's Republic - Gao, Mobo C. F., 1952- (Pluto Press, 2018)
From fear and anxiety, to celebration, China's rise has provoked a variety of responses across the world. In light of this phenomenon, how are our understandings of China produced? From West to East, Mobo Gao interrogates knowledge production; rejecting the supposed objectivity of empirical statistics and challenging the assumption of a dichotomy between the Western liberal democracy and Chinese authoritarianism. By examining issues such as the Chinese Neo-Enlightenment and neoliberalism, national interest vested in Western scholarship, representations of the Great Leap Forward and the Cultural Revolution, and the South China Sea, the book asks: how is contemporary China constructed? By dissecting the political agenda and conceptual framework of commentators on China, Gao provocatively urges those not only on the Right, but also on the Left, to be self-critical of their views on Chinese politics, economics and history.--